Knowledge, awareness, and attitudes toward antibiotic resistance and practice of self-medication among university students in Bangladesh: A cross-sectional study - Gowranga Kumar Paul; Md Shalauddin Swapon; K M Kaderi Kibria (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The prevalence of self-medication is high in Bangladesh due to easy access and poor regulatory controls over these drugs. Our study aimed to assess the attitude of university students in Bangladesh toward antibiotic usage, especially their knowledge and awareness about antibiotics and their resistance. We also evaluated the determinants behind their attempts at drug intake without prescription. MATERIALS AND METHODS: A cross-sectional study was conducted in Mawlana Bhashani Science and Technology University that included information from randomly selected 200 students from 15 departments using a structured questionnaire. The statistical analyses were performed by using SPSS software (version 21) and R programming. RESULTS: The study revealed that 61.0% of the students use self-medication at different times or always; 32.5% of the respondents keep antibiotics for future use, and 38% of the students think it is right to stop antibiotics when symptoms are improving. Half of the participants (47.5%) use antibiotics based on their previous experience. The criteria of antibiotic selection have a significant relationship with knowledge about antibiotic resistance (P = 0.017) and altered prescribed medicine without doctor's advice (P < 0.001). The multivariate analysis indicates that respondents who know about antibiotic resistance select antibiotics from the community pharmacists with respect to their own experience 5.102 times higher than those who do not know about antibiotic resistance. CONCLUSIONS: The study mainly explored the knowledge gaps of the students on the options that are responsible for antibiotic resistance in the community and found that students have mid-level knowledge (66%) about antibiotic resistance.